KORELASI ANTARA UKURAN-UKURAN TUBUH DAN BOBOT BADAN TERNAK KERBAU DI PULAU KABAENA KABUPATEN BOMBANA - Dahlan, Rispan; Nafiu, La Ode; Aku, Achmad Selamet (Pascasarjana Universitas Sulawesi Tenggara, 2019)
This study aimed to obtain information about the quantitative characteristics of body measures include body length, shoulder height, chest circumference, hip height and hips width. Andanalyze the correlation between buffaloes body measurements and body weight in Kabaena IslandBombana. The study done in February-April 2014, Research material were 87 buffaloes consisting of 55 female buffaloes and 32 male buffaloes which is owned by residents in the study area. Thepopulation in this study was the population of buffaloes in three districts on Kabaena island namelyCentral, North and East Kabaena. data were analyzed using Minitab software applications version16th To determine the relationship between body weight, shoulder height, chest circumference, bodylength, hip height, hip width, then followed by a significant test (t test) correlation coefficient (r). Theparameters observedwere body Weight (Bw), shoulder height (SH), chest circumference (CC), bodylength (BL), hip height(HH), hip width (HW). The results showed the adult male buffalo has bodyweight, shoulder height, hip height, chest circumference, body length and hip width respectively of503.83 kg; 126.75 cm; 147.83 cm; 195.92 cm; 147.83 cm; 50 cm. While the adult female buffalo haveweight, shoulder height, hip height, chest circumference, body length and hip width respectively of527.03 kg; 129.89 cm; 128.33 cm; 198.58 cm; 149.86 cm and 53.11 cm. Buffal’s body weight andshoulder height in Kabaena Island Bombana have the strongest relationship with the value of thecorrelation coefficient was r = 0.961. Keywords : Correlation, Body Weight, Body Measurements, Buffalo, Kabaena Island